Bio-inspired, scalable, and tri-mode stimuli-chromic composite for smart window multifunctionality - Ke, Yujie (2024)
Smart window is promising to save building energy and reduce carbon emissions. The fast development leads to a high demand for multifunctionality not limited to energy saving, while the material design and fabrication are challenging. Herein, a scalable method is developed for tri-mode light regulations: thermo-, mechano-, and hydro-/solvato-chromisms. The film is constructed of a bio-inspired hierarchical-structured surface and a functional elastomer base. Through combined experiments and simulations, the triple-stimuli-chromic mechanisms of strain-induced surface structure deformations, wettability-controlled reflective index matches, and thermal-responsive nanostructural resonances, respectively are revealed. Besides a good energy-saving performance, the robust method shows several advantages: 1) independent energy-saving and privacy functionalities, 2) an additional hydro-/solvato-chromic mode to control privacy in extreme circumstances, and 3) designable patterns and colors to meet high aesthetic demand. The work may inspire the future development of multifunctional smart windows and spatio-temporal light control methods.